Management of Velopharyngeal Insufficiency Using Double Opposing Z-Plasty in Patients Undergoing Primary Two-Flap Palatoplasty - Kyung Suk Koh; Sung Chan Kim; Tae Suk Oh (Archives of Plastic Surgery, 2013)
Background Velopharyngeal insufficiency (VPI) may persist after primary repair of the cleft palate, and surgical correction is necessary in many cases. The purpose of this study is to evaluate the effect of double opposing Z-plasty (DOZ) in cleft palate patients suffering from VPI after primary two-flap palatoplasty. Methods Between March 1999 and August 2005, we identified 82 patients who underwent two-flap palatoplasty for cleft palate repair. After excluding the patients with congenital syndrome and mental retardation, 13 patients were included in the final study group. The average age of the patients who underwent DOZ at was 5 years and 1 month. Resonance, nasal emission, and articulation were evaluated by a speech pathologist. The velopharyngeal gaps were measured before and after surgery. Results Six patients attained normal speech capabilities after DOZ. The hypernasality grade was significantly improved after surgery in all of the patients (P=0.0015). Whereas nasal emission disappeared in 8 patients (61.5%), it was diminished but still persisted in the remaining 5 patients. Articulation was improved in all of the cases. In two cases, the velopharyngeal gap was measured using a ruler. The gap decreased from 11.5 to 7 mm in one case, and from 12.5 to 8 mm in the second case. Conclusions The use of DOZ as a surgical option to correct VPI has many advantages compared with other procedures. These include short surgery time, few troublesome complications, and no harmful effects on the dynamic physiological functioning of the pharynx. This study shows that DOZ can be another option for surgical treatment of patients with VPI after two-flap palatoplasty.